A Multilevel Factor Model for Economic Activity with Observation Driven Dynamic Factors - Mariia Artemova; Francisco Blasques; Siem Jan Koopman (Tinbergen Institute, 2023)
We analyze the role of industrial and non-industrial production sectors in the US economy by adopting a novel multilevel factor model. The proposed model is suitable for high-dimensional panels of economic time series and allows for interdependence structures across multiple sectors. The estimation procedure is based on a multistep least squares method which is simple and fast in its implementation. By analyzing the shock propagation process throughout the network of interconnections, we corroborate some of the key findings about the role of industrial production in the US economy, quantify the importance of propagation effects and shed new light on dynamic sectoral linkages.
Keywords: C22; C32; C38; C51; 330; Dynamic factor model; Interconnectedness; Output growth.